Role of prescribed medication in the development of iron deficiency anaemia in adults—a case–control study - Orouba Almilaji; Jonathon Snook; Kiran Prabhu; Elizabeth Williams; Frazer Warricker (BMJ Open Gastroenterology)
Objective To estimate the strength of association between exposure to selected classes of prescribed medications and the risk of developing iron deficiency anaemia (IDA), specifically considering oral anticoagulants (OACs), antidepressants, antiplatelet agents, proton pump inhibitors (PPIs) and non-steroidal anti-inflammatories.Design A case–control study involving the analysis of community repeat prescriptions among subjects referred with IDA, and unmatched controls referred as gastroenterology fast-tracks for other indications. Multivariable logistic regression modelling was used to calculate ORs for the association between IDA presentation and each medication class, adjusted for age, sex and coprescribing. For those classes showing significance, it was also used to calculate risk differences between those in the IDA group with or without haemorrhagic lesions on investigation.Results A total of 1210 cases were analysed—409 in the IDA group, and 801 in the control group. Significant associations were identified between presentation with IDA and long-term exposure to PPIs (OR 3.29, 95% CI: 2.47 to 4.41, p<0.001) and to OACs (OR 2.04, 95% CI: 1.29 to 3.24, p=0.002). IDA was not associated with long-term exposure to any of the other three drug classes. In contrast to the relationship with PPIs, the association with OACs was primarily in the IDA sub-group with haemorrhagic lesions.Conclusion Long-term exposure to PPIs and OACs are independently associated with the risk of developing IDA. There are grounds for considering that these associations may be causal, though the underlying mechanisms probably differ.